(untitled) (Journal of Basic and Applied Sciences, 2023)
This paper implements and tests one type of renewable energy, solar energy. Enhancing the performance and efficiency of these sources has become increasingly important to compete with traditional fossil fuel sources in terms of efficiency, power quality, and production cost. The project explains in detail the methods used to increase solar energy efficiency. The primary approach is the sun tracking system, which continuously directs the solar panels toward the sun to maximize direct solar irradiation. Additionally, maintaining the optimal temperature for photovoltaic (PV) cells improves efficiency and prolongs their lifespan, achieved by integrating a cooling system with the sun tracking system. PV cells are sensitive to temperature variations. Increased ambient temperature and solar irradiance raise the PV cells’ operating temperature, reducing open-circuit voltage, fill factor, and power output for mono- and polycrystalline PV cells, potentially causing irreversible damage. Proper cooling is necessary to maintain operating temperature within manufacturer-specified values. This review presents passive cooling methods (heat pipe and fins) to enhance the performance of commercial PV and concentrated photovoltaic (CPV) cells. Results indicate that using the mentioned methods, solar panel efficiency improved by 15% with the tracking system, and after cooling, efficiency reached approximately 85%.